Peran Sosial Guru Pendidikan Agama Islam Di Wilayah Pesisir Utara Pulau Jawa - Arum Yuli Dwi Rahmawati; Muhammad Nasruddin; Imroatun Imroatun (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2020)
This article seeks to qualitatively identify non-formal Islamic religious education in the coastal areas of the large island of northern Java, particularly regarding the social role of Islamic education teachers at the primary education level in the village of Demangharjo, Tegal Regency, including the problems they carry out. Data were collected by direct observation and direct interviews with elementary Islamic education teachers involved in non-formal Islamic education activities in village mosques. Triangulation in data collection methods derived from observations and interviews was chosen for validity before being analyzed with an interactive model, from data collection, data reduction, to drawing conclusions. This research concludes that the role of SD-level Islamic education teachers in informal education in the northern coastal areas is unique in that it combines the findings about the role of teachers in villages in island coastal areas and inland urban areas by considering the uniqueness of Demangharjo village as a research area. The problem is indeed multidimensional, but it is suggested that the direct involvement of parents of students in the provision of informal education is in addition to the need for incentives from stakeholders. This PAI research can still be developed because the social conditions in each region still require further exploration even though in similar geographical conditions.